2016
DOI: 10.1177/1756287216629870
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with radium-223 in the treatment of patients with advanced castrate-resistant prostate cancer and symptomatic bone metastases

Abstract: The treatment of metastatic castrate-resistant prostate cancer (mCRPC) has grown over the past decade. The majority of patients develop bone metastases, which pose a significant burden on morbidity and mortality, especially skeletal-related events. Whilst demonstrating a favourable safety profile and improving symptoms, radiopharmaceuticals have until recently failed to show a survival benefit. However, since the large phase III randomized ALSYMPCA trial, the calcium mimetic properties of radium-223 (Ra223) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
5
10
0
Order By: Relevance
“…The overall median survival of 10.5 months for Ra-223 patients observed here is inferior to that reported for both the Ra-223 and the placebo groups (14.9 vs. 11.3) in the ALSYMPCA trial. Other real world retrospective studies have reported median overall survival ranging from 8.3 months to 12.9 months [7][8][9], in-keeping with that observed in this cohort.…”
Section: Discussionsupporting
confidence: 90%
“…The overall median survival of 10.5 months for Ra-223 patients observed here is inferior to that reported for both the Ra-223 and the placebo groups (14.9 vs. 11.3) in the ALSYMPCA trial. Other real world retrospective studies have reported median overall survival ranging from 8.3 months to 12.9 months [7][8][9], in-keeping with that observed in this cohort.…”
Section: Discussionsupporting
confidence: 90%
“…The advanced extent of disease of the study population could have been the reason for the high incidence of hematologic toxicity relative to that in the existing literature (14,(24)(25)(26). In particular, thrombocytopenia was frequent and was associated with a complete lack of recovery within 6 mo despite the discontinuation of 223 RaCl 2 .…”
Section: Discussionmentioning
confidence: 95%
“…223 Ra-Dichloride is a targeted alpha-emitter therapy that mimics calcium and targets areas of increased bone turnover. Alpha particles have a very short range (<100 ÎŒm), so damage to surrounding tissues is minimal [ 9 ]. Prior to the introduction of 223 Ra-dichloride, bone-targeting therapies did not lead to longer overall survival (OS); the benefits were primarily limited to pain relief and delay of skeletal events [ 10 ].…”
Section: Introductionmentioning
confidence: 99%